ANALISIS PERSONAL HYGIENE DAN SARANA SANITASI TERHADAP RISIKO SCABIES PADA SANTRI - Novia Pramudita, Putri; Kholid Fauzi, Ahmad; Munir, Zainal (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Scabies is a common health problem in Islamic boarding schools, primarily caused by poor personal hygiene practices and inadequate sanitation facilities. These conditions increase the risk of disease transmission in densely populated environments. Objective: This study aimed to analyze the relationship between personal hygiene and sanitation facilities with the incidence of scabies among students. Methods: This study used an analytical design with a cross-sectional approach. The population consisted of all students living in the boarding school, totaling 280 individuals, using a total sampling technique. Data were collected using questionnaires and analyzed using the chi-square test. Results: The results showed that most students had poor personal hygiene behaviors and inadequate sanitation facilities, and the majority experienced scabies. Statistical analysis indicated a significant relationship between personal hygiene and scabies incidence (p-value ≤ 0.05), as well as between sanitation facilities and scabies incidence (p-value ≤ 0.05). Conclusion: Poor personal hygiene and inadequate sanitation facilities are associated with an increased risk of scabies incidence. Therefore, improving health education on clean and healthy living behaviors and enhancing sanitation facilities are essential to prevent and reduce scabies cases in boarding school environments.